EFFECT OF FLUSH VOLUME ON GENTAMICIN DELIVERY THROUGH UMBILICAL VENOUS CATHETERS. Issue 1 (14th December 2015) - Lala, Anita; Reith, David; Broadbent, Roland; Medilcott, Natalie
Abstract : Background: Intravenous gentamicin is frequently prescribed for the treatment of early-onset sepsis to premature neonates. Background infusion rate and flush volume are known to influence gentamicin delivery and we aimed to further quantify these factors. Methods: Intravenous infusions were designed to simulate gentamicin delivery through umbilical venous catheters with a constant background flow rate of 0.5 mL/hr. Doses of gentamicin (2 mg or 5 mg) were administered by bolus injection over 3–5 minutes followed by a flush of 0.9% saline (1 mL or 2 mL). Samples were collected at 5 minute intervals for 1 hour and analysed by high pressure liquid chromatography. Results: Complete recovery of 2 mg and 5 mg doses was observed following administration of both flush volumes. Of the 2.15 mg recovered when a 1 mL flush is used, 85% (standard deviation, SD, 3.1%) was collected by 10 minutes and 93% (SD 1.4%) over the first 30 minutes. When a 2 mL flush is given, 99% (SD 0.5%) of the 1.88 mg administered dose is recovered in 10 minutes. Following a 5 mg intended dose, 93% (SD 3.4%) is recovered at 10 minutes and 97% (SD 2%) in 30 minutes after a 1 mL flush, compared to 99% (SD 0.6%) recovery at 10 minutes with a 2 mL flush. Conclusion: Simulated gentamicin delivery by bolus injection into slow-flowing neonatal central lines resulted in >90% dose recovery at 1 hour. Additionally, discrepancies between intended and actual gentamicin dose, and retrograde flow of dye was observed.